Drivers of seasonal and diurnal particulate material load patterns in northern Norwegian fjords : using ADCP backscatter to contribute to improvement of baseline knowledge and management - Blom, Menno Jelle Johannes, 1996- (2021)
Verkefnið er lokað til 17.06.2022. Anthropogenic activity and a resulting need for coastal management are increasing in northern Norwegian fjords. This study aims to enhance baseline environmental knowledge by identifying environmental and anthropogenic drivers of material load patterns in two ice free subarctic fjords to contribute to the improvement of northern Norwegian coastal management. Range normalized backscatter data from moored ADCPs is combined with vertical particle fluxes from long- and short-term sediment traps and other fjord parameters such as meteorology, hydrography, and aquaculture activity gathered over a 6-to-10-month period. Time series analysis identifies environmental and biological drivers of material load patterns. The study verifies that backscatter can be used to detect seasonal and diurnal patterns in material load in the water column of northern Norwegian fjords. Environmental drivers of material load show seasonal relationships to biological production, advection, hydrography, meteorological and light conditions. Diurnal patterns of material load appear to be driven by Diel Vertical Migration (DVM) of zooplankton and vary seasonally. Effects of aquaculture activity on material load was masked by other drivers, i.e. DVM and biological production. The monitoring of particulate material load by ADCPs is a potentially valuable method for multidisciplinary interannual monitoring and to support ecosystem-based management. The method can be an effective tool for monitoring of zooplankton and interaction with (zooplankton) fisheries. Additionally, short- and long-term monitoring of aquaculture waste deposition with ADCPs could contribute to sustainable management of the aquaculture industry. Stranbúskapur á fjörðum í Norður Noregi hefur aukist sem eykur kröfur til stransvæðastjórnunar. Þessi rannsókn og útttekt hefur það að markmiði að auka við þekkingu á viðmiðunargildum fyrir umhverfisaðstæður þar sem áhrif stranbúskapar geta haft umbreytandi áhrif á aðstæður í tveimur íslausum ...